Strategy Development: Most Signficant Change (MSC) Toolkit (ODI, 2009)
The Most Significant Change (MSC) technique is a form of participatory monitoring and evaluation. It is participatory because many project s takeholders are involved both in deciding the sorts of change to be re corded and in analysing the data. It is a form of monitoring because i t occurs throughout the programme cycle and provides information to he lp people manage it. MSC contributes to evaluation because it provides data on impact and outcomes which can be used to help assess the perf ormance of the programme as a whole. Essentially, the process involves the collection of significant change (SC) stories emanating from the field level, and the systematic selection of the most important of the se by panels of designated stakeholders or staff. The designated staff and stakeholders are initially involved by ‘searching’ for project im pact. Once changes have been captured, various people sit down togethe r, read the stories aloud and have regular and often in-depth discussi ons about the value of the reported changes. When the technique is suc cessfully implemented, whole teams of people begin to focus their atte ntion on programme impact. MSC has had several names since it was conc eived, each emphasising a different aspect. Examples are: ‘Monitoring- without-indicators’ – MSC does not make use of predefined indicators, especially ones which have to be counted and measured; or the ‘story a pproach’ – the answers to the central question about change are often in the form of stories of who did what, when and why, and the reasons the